Groundwater and surface water connectivity within the recharge area of Guarani aquifer system during El Niño 2014–2016 - Batista, Ludmila (2018)
Recharge areas of the Guarani Aquifer System (GAS) are particularly sensitive and vulnerable to climate variability; therefore, the understanding of infiltration mechanisms for aquifer recharge and surface run‐off generation represent a relevant issue for water resources management in the southeastern portion of the Brazilian territory, particularly in the Jacaré‐Pepira River watershed. The main purpose of this study is to understand the interactions between precipitation, surface water, and groundwater using stable isotopes during the strong 2014–2016 El Niño Southern Oscillation event. The large variation in the isotopic composition of precipitation (from −9.26‰ to +0.02‰ for δ18O and from −63.3‰ to +17.6‰ for δ2H), mainly associated with regional climatic features, was not reflected in the isotopic composition of surface water (from −7.84‰ to −5.83‰ for δ18O and from −49.7‰ to +33.6‰ for δ2H), mainly due to the monthly sampling frequency, and groundwater (from −7.04‰ to −7.76‰ for δ18O and from −49.5‰ to −44.7‰ for δ2H), which exhibited less variation throughout the year. However, variations in deuterium excess (d‐excess) in groundwater and surface water suggest the occurrence of strong secondary evaporation during the infiltration process, corresponding with groundwater level recovery. Similar isotopic composition in groundwater and surface water, as well as the same temporal variations in d‐excess and line‐conditioned excess denote the strong connectivity between these two reservoirs during baseflow recession periods. Isotopic mass balance modelling and hydrograph separation estimate that the groundwater contribution varied between 70% and 80%, however, during peak flows, the isotopic mass balance tends to overestimate the groundwater contribution when compared with the other hydrograph separation methods. Our findings indicate that the application of isotopic mass balance methods for ungauged rivers draining large groundwater reservoirs, such as the GAS outcrop, could provide a powerful tool for hydrological studies in the future, helping in the identification of flow contributions to river discharge draining these areas.